Wolf-Bison Interactions in Yellowstone National Park - Smith, Douglas W.; Mech, L. David; Meagher, Mary; Clark, Wendy E.; Jaffe, Rosemary; Phillips, Michael K.; Mack, John A. (Oxford University Press, 2000)
We studied interactions of reintroduced wolves ( Canis lupus ) with bison ( Bison bison ) in Yellowstone National Park. Only 2 of 41 wolves in this study had been exposed to bison before their translocation. Wolves were more successful killing elk ( Cervus elaphus ) than bison, and elk were more abundant than bison, so elk were the primary prey of wolves. Except for a lone emaciated bison calf killed by 8 1-year-old wolves 21 days after their release, the 1st documented kill occurred 25 months after wolves were released. Fourteen bison kills were documented from April 1995 through March 1999. All kills were made in late winter when bison were vulnerable because of poor condition or of bison that were injured or young. Wolves learned to kill bison and killed more bison where elk were absent or scarce. We predict that wolves that have learned to kill bison will kill them more regularly, at least in spring. The results of this study indicate how adaptable wolves are at killing prey species new to them.